PENERAPAN METODE SIX SIGMA DALAM ANALISIS KUALITAS PRODUK (Studi Kasus Produk Batik Handprint Pada PT XYZ di Bali) - PUTRA, TRI ALIT TRESNA; SUKARSA, I KOMANG GDE; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 6 No 2 (2017), 2017)
The aim of this study was to demonstrate the application of Statistics Quality Control in fierce industries. By observing Batik production process at PT XYZ as a case in this work, we applied Six Sigma Method to analyze defective product and their cause while also measure overall quality goodness. Six Sigma is a method to improve a process and reduce defects in productions into 3.4 defects per million productions. We use handprint batik productions at PT XYZ as a case in this study. The method is involving Define, Measure and Analyze (DMA) phases. By using Six Sigma, it was obtained that the quality of handprint batik are quite good with sigma of 3.105 and defect rate of 54.269 million production (DPMO). There are four defect causes of handprint batik namely: ripped fabric, shallowness, perforation, and mispattern which contribute 41,7%, 35,8%, 15%, 7,5% respectively from overall defects. The main cause of defects is the carelessness of workers in production process. Therefore we need to reduce the carelessness to  improve production quality.